Da'wah Strategy of the Tabligh Majelis Of Muhammadiyah Padang Sidempuan Regional Leadership in Fostering Religious Harmony - Harahap, Rizky Fadli; Soiman, Soiman (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2024)
This research is entitled